UJI KONSISTENSI PENENTUAN NILAI SAHAM-SAHAM INDUSTRI PROPERTI DAN REALESTATE YANG TERDAFTAR DI BURSA EFEK JAKARTA - Dr. David Sukardi Kodrat, MM (EKUITAS (Jurnal Ekonomi dan Keuangan), 2007)
The purpose of this research is to know whether profit growth, dividend payout ratio and deviation standard are determining the fair of stock price among period The population of the research is go public companies and samples taken are property and realestate industries already listed before January 1995 and the companies still listed on the Jakarta Stock Exchange still December 31th, 1999. The Data used in this research is secondary data i.e. Earning Per Share (EPS), Price Earning Ratio (PER) and standard deviation of each company from 1995 until 1997 as independent variables.The result of this research shows that: (1) profit growth, dividend payout ratio and deviation standard are together have real impact on price earning ratio, (2) among variables believed to price earning ratio predictors, profit growth, dividend payout ratio and deviation standard i.e 15.3%, 17.2% and 15.4% and (3) this research shows that the dominant impact of variables are different among period. The differences were in the significance level and the weight of influence of independent variable to the corresponding dependent variable. On the 1995, the influence variable is standard deviation but on the 1996 and 1997 the influence variable is profit growth.